Program Tangguh Mental melalui Anger Management Training (PTM AMT) - Lilis Suryani; Dwi Retno Wati; Sukati Sarmin; Zeny Fatmawati (Rena Cipta Mandiri, 2024)
The phenomenon of childbirth from year to year with the increasing caesarean section method and increasingly sophisticated caesarean section methods has made the scope of midwifery services narrower. One method that is currently being developed is the Eracs method of delivery by caesarean section. Where with this method many pregnant women are tempted by the word